Fate of the microbial population and the physico-chemical parameters of "Sanganel" a typical blood sausages of the Friuli, a north-east region of Italy. (May 2017) - Iacumin, Lucilla; Manzano, Marisa; Stella, Simone; Comi, Giuseppe
Abstract: In Friuli, a Northeastern region of Italy, a blood sausage called Sanganel is produced by farmers, butchers, shops, and factories. This sausage is made with pork meat, boiled blood, lard, spices, and salt. It is stored at 4 ± 2 °C and usually eaten fresh or boiled within 14 days of its manufacture. Little is known about its microbial populations and safety for consumption. The aim of this study is to characterise the microbial populations and the physico-chemical parameters of Sanganel to establish its quality and the safety of consuming it. The microbial population of Sanganel is typical of meat products, and psychrotrophic enterobacteria and lactic acid bacteria (LAB) grow while it is stored. Enterobacteria produce total basic volatile nitrogen (TVB-N) and biogenic amines that, despite the presence of LAB, increase the pH of the sausage to approximately 6.9. Considering the concentrations of Enterobacteriaceae and TVB-N in the sausage, a shelf-life of 14 days is suggested. However, at 30 days the sausage is safe to eat and presents normal odours and flavours. In addition, boiling the sausage for 30 min before consumption eliminates the asporogenous microbial population. Highlights: Sanganel is a fresh traditional blood sausages of Italy. No pathogenic microorganisms are present. Low TVB-N and biogenic amines concentration. It is storaged till about 14 days. It is safe.